2015
DOI: 10.1503/cjs.012314
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of VTE postdischarge for major abdominal and pelvic oncologic surgery: implications for a change in practice

Abstract: Background: Extended thromboprophylaxis after hospital discharge following cancer surgery has been shown to reduce the incidence of venous thromboembolism (VTE); however, this practice has not been universally adopted. We conducted a populationbased analysis to determine the proportion of patients with symptomatic VTE diagnosed within 90 days after initial discharge following major abdominopelvic cancer surgery who might have benefited from extended thromboprophylaxis. Methods:We used the Manitoba Cancer Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…However, the use of NOACs for VTE prophylaxis is certainly debatable. Potential drug interactions with chemotherapeutic components, GI abnormalities, and hepatic and renal insufficiency remain significant determinants of NOAC administration[ 43 - 45 ]. Therefore, bioavailability may not reach desirable levels[ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of NOACs for VTE prophylaxis is certainly debatable. Potential drug interactions with chemotherapeutic components, GI abnormalities, and hepatic and renal insufficiency remain significant determinants of NOAC administration[ 43 - 45 ]. Therefore, bioavailability may not reach desirable levels[ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…16,21 The risk of VTE, however, extends beyond discharge: at least 30% to 50% of postoperative VTE events occur in the outpatient setting. 2,3,6,7 Patients with underlying malignancy or IBD are at particularly elevated risk. 3,6 Despite more than a decade of strong evidence to support its use, post-discharge prophylaxis remains under-used in practice.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Critically, however, at least 30% to 50% of VTEs occur after discharge for patients undergoing abdominal surgery for malignancy or IBD. 2,3,6,7…”
mentioning
confidence: 99%
“…From observational/retrospective studies, it has been shown that the risk of thromboembolic events remains high for at least 30 days postoperatively and even up to 3 months after discharge. The ratio can be even 10-50 times higher compared to controls and a retrospective review of medical records for newly discharged surgical patients revealed that more patients presented to hospital with signs and symptoms of VTE in the first 3/12 after their discharge compared to the number of inpatients diagnosed (39,40). In another similar study the mean time to DVT was approximately 65 days after discharge (25).…”
Section: Duration Of Prophylaxismentioning
confidence: 93%